Ontogeny and phylogeny of the cercopithecine cranium: A geometric morphometric approach to comparing shape change trajectories. Issue 124 (November 2018) - Simons, Evan A.; Frost, Stephen R.; Singleton, Michelle
Abstract: While the analysis of ontogenetic trajectories is common in geometric morphometrics (GM), the simultaneous comparison of several trajectories can be unwieldy and is, in some cases, unable to make use of one of the main advantages of GM, visualization. Furthermore, due to the paucity of the paleontological record, analyses of trajectories are often limited to extant taxa. We address these issues by presenting a method for visualizing the similarities and differences of cranial ontogenetic trajectories among taxa and a method for reconstructing ancestral ontogenetic trajectories, so that these differences can be investigated in a phylogenetic context. We also tested for the presence of phylogenetic signal in the ontogenetic trajectories themselves. Using an ontogenetic series of 522 crania, representing 17 cercopithecine species from 8 genera, we first calculated ontogenetic trajectories of cranial shape change for each species, and then entered these trajectories into a principal components analysis to produce a developmental shape-change trajectory PCA (δPCA). Then, through an augmentation of the phylomorphospace approach, we projected a molecular phylogeny onto the major axes of trajectory shape variation from the δPCA to produce an 'ontophylomorphospace, ' using squared-change parsimony to reconstruct interior nodes. Through these procedures, we were able to determine that the δPCAs illustrate patterns of variation in these developmental trajectories in a visually intuitive manner that allows for easier comparisons among taxa. Through examination of the ontophylomorphospace, we found that African papionins exhibit extensive homoplasy in the evolution of cranial ontogenetic trajectories, and that Asian species of Macaca show highly derived ontogenetic trajectories relative to other cercopithecines. Additionally, we found no support for the presence of a phylogenetic signal in cranial ontogenetic trajectories. The δPCA and the ontophylomorphospace are ways in which to visualize and compare complex, multivariate shape transformations, both among extant taxa and over evolutionary time, respectively.